Addressing puma-livestock conflicts across the Americas - Lucherini, Mauro (2023)
The puma (Puma concolor) is the most widespread apex carnivore across the American continent. Their ecological adaptability has enabled pumas to survive in anthropogenically modified areas but has also frequently put them in conflict with a still expanding livestock industry, especially in Latin America. Although puma-livestock conflicts are widespread and threaten heavily this felid?s role in ecosystems, our comprehension of the factors trigging them and their consequences for both components of the conflict equation is still poor. We will present a global review (92 papers from 14 countries) on the geographic, anthropogenic, and habitat characteristics that conflict areas have in common, indicating that conflicts are primarily located in the Southern Hemisphere and characterized by high densities of livestock. We will revise the scattered data available on the magnitude and monetary impact of the losses caused by puma predation on livestock in the context of local economies, including the little-explored phenomenon of surplus killing, to show that the impact is typically small but can be locally disruptive. We will use a global database (84 papers covering 102 sites from 15 countries) to assess the importance of livestock compared to wild prey (introduced and native) in the diet of pumas. We will show that while puma diet included 211 distinct species globally, only 31 species had a mean frequency of occurrence in diet greater than 5% or occurred in more than five study sites. The great majority of these species was large or medium-sized, but only two were domesticated (sheep and cow). The introduced European hare is the most widespread puma prey. Finally, we will discuss the lack of evidence of the efficacy of lethal control of puma populations (which is one of the most widespread conflict reduction strategies) to mitigate conflict with ranchers.